2016
DOI: 10.1016/j.agee.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mulching on above and below ground pests and beneficials in a green onion agroecosystem

Abstract: In 2013 and 2014, different mulching systems were investigated for their potential to suppress above and below ground pests, and enhance beneficial arthropods and soil health in green onion (Allium cepa) plantings. Three types of mulch systems (organic, living and solarization mulch) were evaluated and compared. Green onions were grown in four pre-plant treatments: 1) organic mulch generated by flail mowing a sunn hemp (Crotalaria juncea) cover crop (SH) followed by a no-till cropping system, 2) soil solarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 75 publications
1
11
0
3
Order By: Relevance
“…populations, it has been observed that the use of conservation strategies such as organic mulching can increase soil diversity and ultimately decrease populations of other pest organisms or their negative effect on crop plants. In several cases, the use of organic amendments has been shown to reduce populations of organisms considered to be pests such as phytoparasitic nematodes (e.g., [74][75][76][77][78]), and phytophagous mites (e.g., [79]), as well as damage by some phytophagous insects (e.g., [80]), and the increase of organisms considered beneficial such as free-living nematodes (e.g., [74,76,78,80]) and predatory mites (e.g., [74,75,79]). At laboratory level and on a small scale, it has been shown that, for some organisms such as some predatory mite species, the addition of alternative such as free-living nematodes can enhance their survival and reproduction and, in turn, their densities [81][82][83], which would be reflected in an increase in the control of phytophagous organisms [82,83].…”
Section: The Importance Of a Holistic Approach For Better Pest Manage...mentioning
confidence: 99%
See 1 more Smart Citation
“…populations, it has been observed that the use of conservation strategies such as organic mulching can increase soil diversity and ultimately decrease populations of other pest organisms or their negative effect on crop plants. In several cases, the use of organic amendments has been shown to reduce populations of organisms considered to be pests such as phytoparasitic nematodes (e.g., [74][75][76][77][78]), and phytophagous mites (e.g., [79]), as well as damage by some phytophagous insects (e.g., [80]), and the increase of organisms considered beneficial such as free-living nematodes (e.g., [74,76,78,80]) and predatory mites (e.g., [74,75,79]). At laboratory level and on a small scale, it has been shown that, for some organisms such as some predatory mite species, the addition of alternative such as free-living nematodes can enhance their survival and reproduction and, in turn, their densities [81][82][83], which would be reflected in an increase in the control of phytophagous organisms [82,83].…”
Section: The Importance Of a Holistic Approach For Better Pest Manage...mentioning
confidence: 99%
“…increase of organisms considered beneficial such as free-living nematodes (e.g., [74,76,78,80]) and predatory mites (e.g., [74,75,79]). At laboratory level and on a small scale, it has been shown that, for some organisms such as some predatory mite species, the addition of alternative such as free-living nematodes can enhance their survival and reproduction and, in turn, their densities [81][82][83], which would be reflected in an increase in the control of phytophagous organisms [82,83].…”
Section: The Importance Of a Holistic Approach For Better Pest Manage...mentioning
confidence: 99%
“…A cobertura morta visa minimizar as perdas de água do sistema para a atmosfera, com a inserção de materiais orgânicos (palhadas, resíduos vegetais, etc.) ou inorgânico (plástico) sobre o solo, buscando-se aumentar o rendimento das culturas agrícolas (Quintanilla-Tornel et al, 2016;Alves et al, 2018).…”
Section: Cobertura Morta Em Sistemas Agrícolas Do Semiáridounclassified
“…Com o intuito de potencializar o aproveitamento da água aplicada no sistema, a inserção de cobertura morta sobre o solo contribui para a redução das percas de água pela evaporação, além de disponibilizar nutrientes com sua mediante decomposição para o solo, e com isso promovendo ecossistemas mais sustentáveis para a produção vegetal no semiárido brasileiro (Quintanilla-Tornel et al, 2016;Alves et al, 2018).…”
Section: Introductionunclassified
“…Mulching is a form of cover crops that remains on the surface of the soil. It can be inorganic or organic material (plastic, straw, cover crop residues or live plant) and it is used to prevent soil erosion, increase water retention, pest control and weed control [10,68,69,70]. However, few of the surveyed farmers are using this method.…”
Section: Typology Of Farms Located On Vertisolsmentioning
confidence: 99%